Early Childhood Development Workforce - Productivity Commission (Media and Publications - Productivity Commission, 2011)
The early childhood development sector plays an important role in fostering the education, health and care of young children. Early childhood education and care services are currently the subject of significant reforms nationally. These reforms have substantial implications for the associated workforce. This report, the second of three on education and training workforces, focuses on the early childhood development workforce. It follows the Vocational Education and Training workforce report released in May 2011. The third report, on the Schools workforce, is underway and will be completed in April next year.
Productivity Commission Research Report
Keywords: Health and wellbeing; Childhood and child development; Learning, education and training; Health and wellbeing; Learning, education and training; Childhood and child development